The Effect of Digital Learning Media Based on Wordwall Games on Students’ Learning Outcomes and Learning Motivation at SDN 17 Prabumulih - Popi Ulandari; Nila Kesumawati; Putri Dewi Nurhasana (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
This paper examines the effect of Wordwall game-based digital media on students’ learning outcomes and learning motivation in fractional material. Wordwall game digital media is an interesting application that creates an active learning atmosphere through learning while playing, thereby increasing student motivation and learning outcomes. The research employed an experimental method using a Posttest-Only Control Design. The population consisted of 334 students, with purposive sampling used to select 28 students of class IIIA as the experimental class and 28 students of class IIIB as the control class. Data were collected through tests and questionnaires. The results show that there is a significant effect of Wordwall game-based digital learning media on students’ learning outcomes in fractional material with a significance value of 0.000, and there are differences in learning outcomes based on students’ learning motivation with a significance value of 0.000. However, there is no interaction between Wordwall game-based digital learning media and students’ learning motivation on learning outcomes in fractional material, as indicated by a significance value of 0.788 at SDN 17 Prabumulih.